Experiencing and understanding the Minangkabau culture as part of architectural education experience - Denan, Zuraini; Abdul Majid, Noor Hanita; Abdul Rahim, Zaiton (2009)
Living within one community is one of the best methods to experience and learn architecture effectively. Heritage Studies (AAR 3301) course is one of the compulsory courses in Bachelor of Science in Architectural Studies program in International Islamic University Malaysia, that enable students to experience the life of one community in order to document its architecture, history and culture through fieldwork of the educational trip. The recent educational trip to Minangkabau village in Pariangan, West Sumatera is one of the most eye opening and unforgettable experience for the students. Twenty-nine (29) students were set out to learn and appreciate the Minangkabau architecture, the custom (adat) that influence the architecture and most importantly the basic structure to survive in everyday life. To achieve the requirements of the course, students documented their field work, research and experience through measured drawing, report, multimedia presentation and exhibition. The students’ experience was also surveyed in order to understand the student’s emotional response. The paper presents students’ outcome of the heritage studies course and their experience in the Pariangan, a Minangkabau village.